Economic Activity and Provincial Solid Waste Generation in Thailand: Evidence from Satellite-Derived Spatial Analysis - Kitipacharadechatron, Ronnakron; Adithipyangkul, Pudinan (Asian Journal of Applied Economics, 2026)
Background and Objectives: Rapid urbanization, economic growth, and changing consumption patterns have increased provincial solid waste generation in Thailand, while waste-management capacity remains uneven across provinces. Existing studies often rely on aggregate statistics or localized case studies, limiting understanding of the spatial interdependence underlying waste dynamics. Recent advances in geospatial technologies allow satellite-derived indicators, such as nighttime lights, land-surface temperature, urbanization measures, and precipitation, to be used as spatial proxies for economic activity, environmental conditions, and human pressure. This study investigates the spatial interconnections between satellite-derived indicators and provincial solid waste generation across Thailand. Methodology: The study uses provincial solid waste data from the 2024 Annual Report of the Ministry of Natural Resources and Environment and satellite-derived indicators processed through Google Earth Engine. Spatial analysis, including quartile mapping, spatial autocorrelation, and spatial clustering, is applied to examine spatial patterns and dependence. A structural equation model is then used to assess the influence of satellite-derived indices on provincial solid waste generation. Key Findings: The results show that provincial solid waste generation in Thailand is spatially clustered and strongly shaped by geographic context. Satellite-derived indicators, particularly socioeconomic activity, urbanization, and daytime land-surface temperature are positively associated with solid waste generation. In contrast, precipitation shows a modest negative association, suggesting that rainfall may reflect broader climatic and geographic conditions rather than directly intensifying waste generation. The structural equation model indicates that satellite-derived indices collectively explain a substantial share of provincial variation in solid waste generation. Policy Implications: The findings support the use of spatially differentiated waste-management policies that prioritize provinces with high urban, economic, and thermal intensity. Satellite-based monitoring systems can help improve real-time decision-making, infrastructure planning, and provincial waste-management strategies. Policymakers should integrate urban planning, industrial zoning, and climate-responsive approaches to mitigate solid-waste pressures in rapidly developing areas.